Local Media Verification Discipline Practices in the Era Of Information Overload - Cahyono, Muchamad Rudi; Djuraid, Dhimam Abror; Syam Maella, Nurannafi Farni (Universitas 17 Agustus 1945 Surabaya, 2025)
Access to information is becoming so easy and cheap. But the effect, a flood or an information tsunami, can be disruptive, extending the pattern of thought to human behavior. So from that some experts offer a predictive strategy, dealing with the disaster. One of the public instruments that has an important role to play is the journalists. Journalists become information gatekeepers from the public to the public. Because of its crucial role in the circulation of information, in the conduct of the profession, journalists have guidelines set out in UU No. 40 tahun 1999 and the Kode Etik Jurnalistik (KEJ). Verification discipline becomes the essence of journalistic activity. Conducting a disciplinary verification, will greatly determine the quality, validity, and credibility of the information presented. Unfortunately, verification disciplinary practice is sometimes not fully carried out. Including journalists from the area. Using the Bill Kovach & Tom Rosenstiel disciplinary verification concepts outlined in the Kode Etik Jurnalistik (KEJ), as well as the Pedoman Pemberitaan Media Siber (PPMS) on this study will look at how the coverage process, the treatment of sources, up to the practice of the discipline verification of local print and cyber media journalists. Using methods of case study research and comparative studies can deepen and compare journalists of print and cyber media of the region namely Radar Tulungagung and Afederasi.com practise the discipline of verification. But not entirely practiced well, more specifically in treating the source. This is due to factors of online media development, corporate operations and leadership policies